2021
DOI: 10.12659/msm.933204
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics Analysis of the Lower Limbs in 20 Male Sprinters Using the International Society of Biomechanics Six-Degrees-of-Freedom Model and the Conventional Gait Model

Abstract: Background This biomechanics study of the lower limbs aimed to compare the use of the International Society of Biomechanics Six-Degrees-of-Freedom (ISB-6DOF) model and the conventional gait model (CGM), formerly known as the Helen Hayes model, in 20 male sprinters who habitually used the forefoot (FF) or rearfoot (RF) strike modes. Material/Methods We used a motion capture system to compare the difference in lower-extremity joint mechanics between sprinters’ forefoot or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In the sagittal plane, there are no differences between marker sets at the hip in healthy subjects, again the same as in previous studies [ 19 , 24 , 25 , 29 ]. However, the Initial Joint Angle, Peak Extension and ROM at the knee, Peak Dorsiflexion, and ROM at the ankle show the differences between marker sets.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the sagittal plane, there are no differences between marker sets at the hip in healthy subjects, again the same as in previous studies [ 19 , 24 , 25 , 29 ]. However, the Initial Joint Angle, Peak Extension and ROM at the knee, Peak Dorsiflexion, and ROM at the ankle show the differences between marker sets.…”
Section: Discussionsupporting
confidence: 85%
“…These findings are comparable with previous studies [ 19 21 , 24 , 29 ]. In previous studies, some researchers found the differences between marker sets at the knee and hip rotation in the transverse plane [ 19 , 24 , 25 , 29 ], while others also found the differences at the knee in the frontal plane [ 24 , 25 , 29 ]. In this study, the findings in healthy subjects are in agreement with the former, while the findings in OA patients correspond to the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variable selected in this study were ankle angle, moment, and ground reaction force 34 . In data processing, the link coordinate system was established through infrared reflective marks on the body surface of the subject, and the moment and angle of the ankle joint were calculated according to the trajectory change of the movement and the coordinate system.…”
Section: Methodsmentioning
confidence: 99%